The Effect of Organizational Culture and Career Development on Job Satisfaction and Performance of IT (Information Technology)Employees of PT. Chevron Pacific Indonesia in Rumbai, Pekanbaru - Dewinta, Cicilia; Hendriani, Susi; Ganarsih, Raden Lestari (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2020)
This study aims to see and find out the direct and indirect effects of organizational culture and career development on job satisfaction and employee performance. In this study, the population was 147 of all employees of the IT (Information Technology) section of PT. Chevron Pacific Indonesia. The analytical tool used was Path Analysis using the SEM-PLS program for windows. In this study, the sampling method used was census method or saturated sample. It showed that the entire population was sampled. The results of this study indicates that organizational culture and career development effect on job satisfaction. Organizational culture, career development and job satisfaction effect on employee performance. Organizational culture and career development effect on employee performance through job satisfaction.Â